Structured Electronics Design A Conceptual Approach to Amplifier Design - Montagne, Anton J.M (Open textbook library., 2023)
Many people consider analog electronic circuit design complex. This is because designers can achieve the desired performance of a circuit in many ways. Together, theoretical concepts, circuit topologies, electronic devices, their operating conditions, and the system's physical construction constitute an enormous design space in which it is easy to get lost. For this reason, analog electronics often is regarded as an art rather than a solid discipline.